The Effect Of Price Fairness And E- Service Quality On Loyalty With Customer Satisfaction As An Intervening (A Study On Netflix Users) - Heri, Jihan (Social Science Studies, 2023)
The SVoD streaming service industry is currently being widely used by the public. One of the SVoD platforms available is Netflix. Netflix has the highest number of subscribers compared to other similar services, but while all of its competitors are experiencing an increase in the number of subscribers, Netflix is ​​experiencing a decline. Based on this phenomenon, the aim of the authors to conduct this research is to determine the level of loyalty of Netflix customers in Indonesia through price fairness and e-service quality variables with customer satisfaction as an intervening variable. This study uses a type of quantitative research and used data from a questionnaire. Respondents in this study were users of the Netflix service aged 15 to 40 years. Data obtained from 220 respondents were processed using the Path Analysis technique with AMOS 24. The results of the study show that Price Fairness and E-Service Quality have an positive and significant effect on Customer Satisfaction and Loyalty.